Analysis of Public Relations Campaigns to Increase Donor Trust in the Digital Age - Ridheta Citrawijaya, Olivia (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The Balikpapan Rice Infaq Movement (GIB) is a movement managed by the Amil Zakat Baitulmaal Munzalan Indonesia (BMI) Balikpapan Institution. This movement aims to help the welfare of the community, especially the orphans, the poor and those who memorize the Qur'an by distributing a total of tens of kilograms of the best rice every year. In first semester of 2024, there was a decrease in the amount of rice distributed by 2% compared to the first semester of 2023. Based on this, this study seeks to analyze the advantages and disadvantages of BMI Balikpapan's Public Relations (PR) campaign strategy and also provides solutions to increase the trust of donors and prospective donors of GIB Balikpapan in the digital era. In this study, the authors used a qualitative descriptive method, which involved in-depth interviews and direct observation, which resulted in data to be analyzed descriptively. The results of the study show that GIB Balikpapan implements prophetic communication in communicating with donors, both in interpersonal communication and through several digital platforms. The use of multiple digital platforms and prophetic communication plays a transformative role in mobilizing support, maintaining visibility, fostering community engagement, loyalty and donor trust. Meanwhile, to increase donor trust, donor diversity, the number of donors and donations, GIB Balikpapan needs to provide more personalized customer service and apply SEO techniques, utilizing CRM services, Google Ads services and Big Data in its Digital Public Relations campaigns.